Empirical Study Of Foreign Exchange Remittance Of Non-Resident Indians - et. al., Dr. Babasaheb Jadhav, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Remittances sent by migrants are an important component of the development finance for the countries. India has secured position as the world's top beneficiary of remittances with USD 80 million in 2018. The study was done in the Maharashtra State which leads the number in remittance (17%). The study highlighted the foreign exchange remittance behaviour of NRIs. The present study tried to understand the remittance behaviour of NRIs and remittance behaviour with respect to demographic profile.The remittance behaviour is studied with the help of demographic and non-demographic factors such as gender, age, occupation, education, purpose of remittance, frequency of remittance, risk in remittance etc.